Manipulation of the Tn5 transpososome assembly pathway and its effect on reaction dynamics - Blundell-Hunter, George (2018)
Transposable elements are an almost ubiquitous feature in all three domains of life, and are a significant driver of genomic evolution. These discrete genetic elements are capable of mobilisation and amplification, which allows them to multiply. A subset of these elements, the cut-and-paste transposons, excise themselves entirely from the surrounding DNA and integrate themselves elsewhere in the genome. Hsmar1, a cut-and-paste element of the mariner transposon family, was recently investigated to examine the kinetics of the complex formation pathway. This transposase forms a dimer in solution before binding to first one transposon end, then recruiting the other. This pathway, Synapsis by Naked End Capture (S-NEC), is found in both prokaryotes and eukaryotes. Tn5, of the IS4 family, is an example of the alternative pathway, Synapsis by Protein Dimerisation (S-PD). In this pathway, the transposase is monomeric in solution. Each monomer binds to a transposon end independently, before combining to form a synaptic complex. This pathway has been seen widely in prokaryotes, but no eukaryotic elements tested to date employ it. To understand what limitations the complex formation pathway might place upon an S-PD transposase in a eukaryotic genome, the Tn5 transposase was manipulated. Forming the transposase into a single-chain dimer allowed it to mimic S-NEC, an alteration that made it hyperactive in prokaryotes and eukaryotes. As the eukaryotic genome contains chromatin, adapting the Tn5 transposase to this might overcome some of the low activity seen. The fusion of a chromatin binding domain to the transposase was not able to enhance the frequency of transposition, which may suggest that the presence of chromatin is not causing significant inhibition. The results presented in this work suggest two significant conclusions. The first is that the S-NEC reaction dynamics are significantly preferable to S-PD within eukaryotes. The second is that S-PD itself may be a system of regulation of transposition, to prevent activity levels that could be detrimental to the host.